(untitled) (Current Problems in Rail Vehicles, 2021)
The article "Current trends in design of wheels for railway vehicles" deals with wheels for freight wagons, wheels for passenger cars, for locomotives and for trams. In the area of wheels for freight wagons, the wheels of the BONATRANS design school are mostly introduced. In the area of wheels for passenger cars, there are wheels with noise absorbers. Finally, the paper summarizes the design of wheels for locomotives and trams.